2020
DOI: 10.1371/journal.pone.0236277
|View full text |Cite
|
Sign up to set email alerts
|

Low transferrin saturation (TSAT) and high ferritin levels are significant predictors for cerebrovascular and cardiovascular disease and death in maintenance hemodialysis patients

Abstract: Patients with high serum ferritin and low transferrin saturation (TSAT) levels could be considered as presenting with dysutilization of iron for erythropoiesis. However, the long-term safety of iron administration in these patients has not been well established. An observational multicenter study was performed over 3 years. In 805 patients undergoing maintenance hemodialysis (MHD), we defined dysutilization of iron for erythropoiesis in patients with lower TSAT (<20%) and higher ferritin (�100 ng/mL) levels. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 20 publications
0
22
0
1
Order By: Relevance
“…A recent clinical study showed that low transferrin saturation and a high ferritin concentration are predictors of cerebrovascular and cardiovascular disease and mortality in patients undergoing MHD. 25 Notably, we have shown that low TIBC and platelet count are associated with a higher risk of all-cause mortality. Iron use disorders would aggravate any anemia, and thrombocytopenia would increase the risks of bleeding and infection.…”
Section: Discussionmentioning
confidence: 90%
“…A recent clinical study showed that low transferrin saturation and a high ferritin concentration are predictors of cerebrovascular and cardiovascular disease and mortality in patients undergoing MHD. 25 Notably, we have shown that low TIBC and platelet count are associated with a higher risk of all-cause mortality. Iron use disorders would aggravate any anemia, and thrombocytopenia would increase the risks of bleeding and infection.…”
Section: Discussionmentioning
confidence: 90%
“…40 , 41 , 42 Besides, iron-laden macrophages are known to be a proatherogenic phenotype, 43 and their presence in haemodialysis patients may add to the already elevated risk of atherogenesis. 44 , 45 , 46 …”
Section: Discussionmentioning
confidence: 99%
“…Among CKD patients, TSAT ≤20% could be found in patients with absolute iron deficiency or functional iron deficiency (also known as iron-restricted erythropoiesis) ( Gafter-Gvili et al, 2019 ). Also, studies have shown that low TSAT levels are related to an increased risk of cerebrovascular and cardiovascular disease (CCVD) and death compared to patients with normal or higher TSAT levels ( Kuragano et al, 2020 ). Therefore, the increasing level of TSAT, TIBC and total iron suggested that daprodustat may be superior to rhEPO in optimizing iron metabolism for the treatment of anemia in DD-CKD patients.…”
Section: Discussionmentioning
confidence: 99%